Synthesis of nanometer-sized PbZrxTi1-xO3 for gamma-ray attenuation. (January 2021) - Hemeda, O.M.; Eid, M.E.A.; Sharshar, T.; Ellabany, H.M.; Henaish, A.M.A.
Abstract: Nanometer-sized PbZr x Ti1- x O3 powder was fabricated by the tartrate precursor method with different Zr contents, x = 0, 0.25, 0.52, and 0.75. All samples were annealed at 850 °C. These annealed samples were characterized by X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy, high-resolution transmission electron microscopy, and thermogravimetric analysis (TGA). The γ-ray attenuation coefficients of the annealed PbZr x Ti1- x O3 samples were measured as a function of the Zr content for 661.7 keV γ-rays from a 137 Cs source. Positron annihilation spectroscopy was used to study the microstructural changes of the prepared samples. The XRD patterns indicate the presence of a tetragonal perovskite structure with a main peak corresponding to the (101) plane at 2 θ of nearly 31°. The FTIR spectra show the presence of two absorption bands at around 620 and 390 cm −1, which are due to stretching and bending vibrations of the Ti–O bond, respectively. The nanometer-sized structure of synthesized PbZr x Ti1- x O3 particles was confirmed by XRD and TEM. The TGA curves show a high decomposition temperature of more than 800 °C for PbZr0·52 Ti0·48 O3 and more than 650 °C for the other samples. PbZr0.52 Ti0.48 O3 shows the highest γ-ray mass attenuation coefficient among the samples studied. The positron annihilation lifetimes show that the main defect types are Pb monovacancies and Pb–O divacancies, and the samples with x ≥ 0.52 have the lowest average defect density. PbZr0.52 Ti0.48 O3 shows the highest value of the W parameter, which means that the chemical environment of its defects has more core electrons compared with the other samples. Finally, PbZr0·52 Ti0·48 O3 has novel properties for γ-ray shielding. Highlights: Nanometer-sized PbZr x Ti1- x O3 powders were prepared by the tartrate precursor method for gamma-ray shielding. The XRD and FTIR results confirm the formation of nanocrystalline PbZr x Ti1- x O3 with a single-phase perovskite structure. TGA revealed high thermal stability for PbZr0·52 Ti0·48 O3, with the highest decomposition temperature of more than 800 °C. The PAL spectra indicate the defect type in the samples corresponds to Pb monovacancy and Pb–O divacancy. Nanometer-sized PbZr0·52 Ti0·48 O3 can be used as a filler for radiation-shielding composite materials.